Analisis Risiko Keselamatan Kerja pada Kegiatan Operasional dan Bongkar Muat di Terminal Peti Kemas PT. IPC Dwikora Pontianak - Dharmawan, Siti Alyasmin; Arifin, Arifin; Asbanu, Govira Christiadora (Universitas Tanjungpura, 2026)
Dwikora Port Pontianak, one of the main ports in Pontianak City, plays a key role in container-handling operations that involve heavy equipment. These activities carry a substantial risk of significant workplace accidents, as reflected in the recorded accident claim data at the Container Terminal of Dwikora Port Pontianak, including incidents such as workers falling from the vessel’s gangway bridge, head trucks colliding with the portal gate, and containers falling due to a malfunctioning spreader on the Rail Mounted Gantry Crane (RMGC). To minimize workplace accidents, a risk analysis was conducted using a combination of Job Safety Analysis (JSA) and Hazard and Operability Study (HAZOP) to identify hazards and assess risks for each task type, and Fault Tree Analysis (FTA) to determine the root causes of accidents. The results indicate that high-risk levels were identified in work activities involving the Quay Container Crane, Jib Crane, Rail Mounted Gantry Crane, Head Truck, Reach Stacker, and Forklift. These risks were further categorized into slipping, tripping, and falling hazards; struck-by and run-over hazards; and equipment or machinery failure. Most of these accident risks are associated with worker behavior and working conditions, equipment failure, and limited operator visibility. The findings serve as the basis for formulating control measures to improve workplace safety and enhance the system's operational stability.